Do expert tennis players actually demonstrate anticipatory behavior when returning a first serve under representative conditions? A systematic review including quality assessment and methodological recommendations - Aviles, C.; Navia, J. A.; Ruiz, L. M.; Martinez de Quel, O. (Psychology of Sport and Exercise, 2019)
Objectives: The present article aims to (i) critically review and classify the studies on the tennis serve return by the degree of representativeness of the experimental task design, (ii) assess the quality of the studies classified with a high degree of representativeness, (iii) analyze to what extent expert tennis players demonstrate anticipatory behavior when actually performing a first serve return. Design and method: Searches were performed in Web of Science and Scopus up to 31st December 2017. The main search term tennis was combined with four groups of key words: anticipation, perception and action, response time and serve return. Researchers selected 62 studies after applying the inclusion criteria. Subsequently, they were screened by degree of experimental task design representativeness through 6 further criteria. Results: Fifty-four studies were found with a medium to low degree of representativeness (87%) and only 8 studies with a high degree of representativeness (13%). Among those eight studies, only one attained the best methodological quality in terms of variables analyzed and information reported. Also, some methodological recommendations were outlined for future research. Conclusions: After 40 years of research, evidence has not yet been found that expert tennis players move to either side before the ball is hit in representative task conditions. Hence, players do not demonstrate observable anticipatory behavior towards the ball direction on the first serve in tennis, but guide their actions upon the information unfolding around the server`s action and first moments of the ball flight.